Preclinical characterisation of changes in cardiac function and circulating biomarkers following differential irradiation of thoracic volumes - Kuburas, Refik; Ghita-Pettigrew, Mihaela; Walls, Gerard M.; Kerr, Brianna N.; Brown, Kathryn H.; Facchi, Cecilia; McWilliam, Alan; van Herk, Marcel; Williams, Kaye J.; Butterworth, Karl T. (Frontiers in Oncology, 2025)
IntroductionThe heart and lungs are critical organs at risk in patients receiving radiotherapy for thoracic tumours. Preclinical studies in rat models have provided evidence indicating consequential effects of lung radiation on the heart through vascular remodelling which leads to pulmonary arterial hypertension. In this study, we aimed to assess the impact of lung irradiation on a long-term model of cardiac base irradiation that recapitulates clinical observations of the heart base as a radiosensitive region and to understand relationships between cardiopulmonary irradiation and circulating cytokines profiles.MethodsFemale C57BL6J mice were irradiated under CT image-guidance targeting the heart base, right lung or co-irradiation of the heart base and the right lung. Mice were monitored by transthoracic echocardiography for 50-weeks after irradiation with lung histology and cytokine profiling at 10 and 50 weeks.ResultsLung and heart co-irradiation leads to small changes in the cardiac function and histological changes in the right lung with distinct changes in serum cytokines for different irradiated volumes compared to heart irradiation.DiscussionIn contrast to previous studies in rat models, these data demonstrate a minimal contribution of lung irradiation to cardiac response in this model. Understanding the potential interplay between the heart and lungs is important in the context of optimising cardiac dose distributions that may increase lung doses and minimising the impact of lung dose on cardiac function.